Effects of Dietary Supplementation of Lacticaseibacillus Chiayiensis AACE3 on Hepatic Antioxidant Capacity, Immune Factors and Gut Microbiology in Nandan Yao Chicks - Xin Kang; Xin-Dong Li; Cheng-Ying Luo; Wei-Gang Xin; Huan-Yu Zhou; Feng Wang; Lian-Bing Lin (MDPI AG, 2023)
The growing issue of antibiotic resistance has restrained the utilization of antibiotics as growth enhancers in the poultry industry. Probiotics are candidates for replacing antibiotics in the poultry industry. However, probiotics are strain-specific and their efficacy needs to be investigated before applying them. The aim of this study was to assess the positive effects of Lacticaseibacillus chiayiensis AACE3 on the health and gut microbiota of Nandan Yao chicks. The results showed that compared with the blank control (NC) and aureomycin (PC) groups, L. chiayiensis AACE3 increased final body weight (BW), villus height and improved the ratio of villus height to crypt depth in chicken jejunal tissues. L. chiayiensis AACE3 also increased the activity of hepatic antioxidant enzymes (SOD, CAT and T-AOC) and reduced hepatic oxidative damage (MDA). Furthermore, compared to NC, L. chiayiensis AACE3, the activity of intestinal digestive enzymes (i.e., α-amylase, lipase and trypsin) was increased. L. chiayiensis AACE3 upregulated the production of IgA and IgG and downregulated the production of IL-6, IL-1β and TNF-α in chicken serum. Moreover, supplementation of L. chiayiensis AACE3 enhances the diversity of gut microbes. At the phylum level, the abundance of Actinobacteriota and Proteobacteria decreased with L. chiayiensis AACE3 supplementation, while the abundance of Verrucomicrobiota and Bacteroidetes increased. At the genus level, there was an increase in the abundance of potential probiotics Akkermansia, Romboutsia, Subdoligranulum, and Lactobacillus. This study confirms that L. chiayiensis AACE3 is an excellent feed additive as an alternative to aureomycin and offers various advantages for the healthy growth of chickens during the brooding period by positively affecting their gut microbiome.